Contratos comerciais de colaboração: transição entre espécies - Sister, Tatiana Dratovsky (2024)
This work aims to investigate commercial collaboration contracts, specifically with regard to the legal and practical feasibility of, under the aegis of the same contractual relationship, transiting between different contractual types of collaboration. This study focuses on certain types of collaboration contracts, notably atypical distribution contracts, franchise contracts and commercial representation contracts, and examines the principles common to these types of contracts and the rules that apply to each of them. In order to justify the need to seek legal solutions to preserve long-term contractual partnerships, research was carried out in concrete cases extracted from Brazilian jurisprudence. The results of these studies show the uncertainties that permeate the framing of contractual types to practical cases, especially because, not infrequently, after a while since contracting, the terms formalized by the parties in the contractual instruments no longer correspond to the activities actually practiced. This study proposes the creation of contractual mechanisms that facilitate fluid transitions between the contractual types of collaboration addressed, without traumatic ruptures in commercial relations, that is, without the need to terminate a contract, under a certain species, to start a new one, under another species. Such transitions are necessary for partnerships to adapt to natural market changes, which alternate between phases of expansion and contraction, according to demands and opportunities. It is expected that the conclusions of this study will serve as an incentive to the flexibility and sustainability of contractual collaborations, permeated by the same principled environment, thus allowing commercial partnerships to evolve according to the requirements of the external environment